2016
DOI: 10.3390/ijerph13111070
|View full text |Cite
|
Sign up to set email alerts
|

Association between Suicide Ideation and Attempts and Being an Immigrant among Adolescents, and the Role of Socioeconomic Factors and School, Behavior, and Health-Related Difficulties

Abstract: The risk of suicide behaviors in immigrant adolescents varies across countries and remains partly understood. We conducted a study in France to examine immigrant adolescents’ likelihood of experiencing suicide ideation in the last 12 months (SI) and lifetime suicide attempts (SA) compared with their native counterparts, and the contribution of socioeconomic factors and school, behavior, and health-related difficulties. Questionnaires were completed by 1559 middle-school adolescents from north-eastern France in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
0
29
0
1
Order By: Relevance
“…Symptoms and other telltale signs are more easily detected when objective: presence of school difficulties is one such sign. Indeed, according to the literature, school difficulties are linked to mental health vulnerability and suicidal behaviors [4,5,[17][18][19][20][21]. A review of the literature on children's mental health and "school performance", "academic functioning", "school attendance", underlined the early manifestations of every mental health disorder of childhood, as identifiable behaviors affecting and affected by school performance" [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms and other telltale signs are more easily detected when objective: presence of school difficulties is one such sign. Indeed, according to the literature, school difficulties are linked to mental health vulnerability and suicidal behaviors [4,5,[17][18][19][20][21]. A review of the literature on children's mental health and "school performance", "academic functioning", "school attendance", underlined the early manifestations of every mental health disorder of childhood, as identifiable behaviors affecting and affected by school performance" [5].…”
mentioning
confidence: 99%
“…Among teenagers with depression in New-Zeland, Fergusson et al, identified that school truancy and suspension were significantly associated with risk of suicide [20]. Among French teenagers, Chau et al [18] reported that having to repeat a school year, increased risk for suicidal ideation in the last 12 months of interview, by a multiple of 1.51 (1.00-2.31 95% CI), and lifetime suicide attempt, by a multiple of 1.92 (1.21-3.04 95% CI). Walsh and Eggert [23], for their part, found risk for suicidal ideation and suicide attempts to be higher in a population of 14-to 21-year-olds with school difficulties than in the general samples US teens.…”
mentioning
confidence: 99%
“…The consideration of a wide range of topics is needed to better inform decision makers and the medical community [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This includes, but is not limited to: Health screening examinations; community-based/multi-lingual health education and resources for refugees; improved awareness of refugee health disparities; disease tracking and reporting systems; multidisciplinary response to disease outbreaks; refugee utilization or lack thereof of healthcare resources/insurance; barriers to healthcare; health selection/trajectory of refugees; hematologic genetic disorders; chronic and mental health issues; abuse; discrimination; exploitation; infectious diseases; immunization strategies; environmental exposures related to disease; hygiene and sanitation; healthy lifestyle choices; illegal activities/injuries (assault, rape, battery); and assimilation analysis.…”
Section: Moving Toward a Solutionmentioning
confidence: 99%
“…Lalonde, discussing Indigenous First Nations Canadians, describes this as “…the special circumstance of finding oneself tugged by both enculturative and acculturative currents” [20] (p. 139). At present, many NA communities in Montana lack sufficient social, emotional, and financial resources, which may increase suicidal behavior risks [21,22]. Nationwide, Indigenous youth are 2.5 times more likely to experience suicidal ideation or attempts than youth from other racial/ethnic youth groups [23,24].…”
Section: Introductionmentioning
confidence: 99%